Removal of vitamin and mineral supplements from broiler chickens finisher diet - Mochamat, Norasyikin; Idrus, Zulkifli; Soleimani, Abdoreza Farjam (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The present study was carried out to examine the effect of vitamin (vit) and mineral (min) premix removal from finisher diet on performance and serum levels of acute phase proteins (APP) (ovotransferrin, ceruloplasmin and alpha-1 acid glycoprotein) responses in broiler chickens raised under different densities. From day 21 onwards, birds were subjected to one of the following feeding regimens; (i) diet without vit-min-premix from 35-42days; (ii) diet without vit-min-premix from 28-42days; (iii) diet without of vit-min-premix from 21-42 days; and (iv) diet supplemented with adequate vit-min-premix (control). Birds from each feeding regimen were stocked either at 0.100 m2 per bird or 0.067 m2 per bird. Irrespective of stocking density, growth performance was not affected adversely by feeding regimen. Higher stocking density depressed growth performance and elevated serum levels of APP suggesting elicitation of physiological stress response. In conclusion, the results from this study suggest that irrespective of stocking density, vit and min premix can be removed from the diets of broilers from day 21 to 42 with any adverse effect on performance.